1998
DOI: 10.1002/(sici)1097-4652(199806)175:3<348::aid-jcp13>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p42/p44 mitogen-activated protein kinase by angiotensin II, vasopressin, norepinephrine, and prostaglandin F2α in hepatocytes is sustained, and like the effect of epidermal growth factor, mediated through pertussis toxin-sensitive mechanisms

Abstract: Several agents that act through G-protein-coupled receptors and also stimulate phosphoinositide-specific phospholipase C (PI-PLC), including angiotensin II, vasopressin, norepinephrine, and prostaglandin (PG) F2alpha, activated the ERK1 (p44mapk) and ERK2 (p42mapk) members of the mitogen-activated protein (MAP) kinase family in primary cultures of rat hepatocytes, measured as phosphorylation of myelin basic protein (MBP) by a partially purified enzyme, immunoblotting, and in-gel assays. All these agonists indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 87 publications
3
31
0
Order By: Relevance
“…An ability of this pathway to activate Erk1/2 has also been observed in other experimental systems, both with ectopically expressed ␣ 1 receptors (19,27) and in cells endogenously expressing these receptors (25,32,54). In the present system, the mediation is probably initially through elevated Ca 2ϩ levels, as demonstrated in other ␣ 1 -induced systems (19,25,26).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…An ability of this pathway to activate Erk1/2 has also been observed in other experimental systems, both with ectopically expressed ␣ 1 receptors (19,27) and in cells endogenously expressing these receptors (25,32,54). In the present system, the mediation is probably initially through elevated Ca 2ϩ levels, as demonstrated in other ␣ 1 -induced systems (19,25,26).…”
Section: Discussionsupporting
confidence: 64%
“…3A). Also ␣ 1 -induced Erk1/2 activation was mediated in a G i -independent manner, confirming the nonessentially of this mediator protein for Erk1/2 activation (although such an ␣ 1 -pathway has been described in primary hepatocytes (32)). An ability of G i to activate Erk1/2 has been observed in several other systems (7-9, 32), although a noninvolvement of G i in the mediation has also been reported in other G-protein-coupled systems (33,34).…”
Section: Discussionsupporting
confidence: 59%
“…Studies by several laboratories have argued that activation of ERBB1, in addition to exogenous ligand-or ROS-induced activation of the receptor, can be due to the actions of GPCRs, which result in either a paracrine/autocrine form of receptor tyrosine kinase activation or a direct activation of ERBB1 via nonreceptor tyrosine kinases. [15][16][17][18][19][20][21][22][23][24] In our studies, incubation of hepatocytes with either marimastat or GM6001, to inhibit cell surface proteases that release ERBB1 receptor ligands, did not alter conjugated bile acid-induced ERK1/2 and AKT activation (unpublished studies and Zhang et al 30 ), whereas inhibition of Src family tyrosine kinase function blunted activation of ERK1/2 and AKT. These data would suggest a direct intra-membrane interaction between GPCR and ERBB1 activation, and enhanced activity in downstream signaling pathways ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 75%
“…[12][13][14] Several studies over the last 10 years have shown that ligand-independent activation of ERBB1 can occur via G-protein-coupled receptor-induced transactivation. [15][16][17][18][19][20] In these studies, activation of membrane-associated non-receptor tyrosine kinases, such as src family members, has been linked to G-protein-coupled receptors (GPCR)-induced ERBB1 tyrosine phosphorylation as well as activation of the receptors by paracrine mechanisms. Because bile acids have been shown to activate some G-protein-coupled receptors in non-hepatocyte cell types, which has been linked to altered proliferation states, some of our prior data showing activation of the ERK1/2 and AKT pathways could have been influenced by bile acid-induced activation of hepatic GPCRs, which in turn promote activation of receptor tyrosine kinases.…”
mentioning
confidence: 99%
“…3,25 Ang II may also exert some of its effects via G i protein signaling. 26 RGS2 acts as a GTPase activating protein, negatively regulating both G q/11 as well as G i/o proteins by enhancing the termination of the activated G protein state. 18,20,27 Additionally, it has been suggested that RGS2 may act as a downstream effector of the NO-cGMP pathway, resulting in vascular relaxation by attenuating vasoconstrictor signaling, whereas suppression of this mechanism may facilitate development of hypertension.…”
Section: Discussionmentioning
confidence: 99%